"We are anxious to remain anonymous": the use of third party scientific and medical consultants by the Australian tobacco industry, 1969 to 1979. (26th November 2003) - Chapman, S
Abstract : Objective: To document the history of visits to Australia by tobacco industry sponsored scientists and news media reports about smoking and health matters generated by their visits. Design: Systematic keyword and opportunistic website searches of tobacco industry internal documents made available through the Master Settlement Agreement. Results: At least nine sponsored scientists visited Australia from 1969 until 1979. The industry sought to promote the scientists as independent from the industry and on occasion, scientists publicly lied about their industry connections. The industry was sometimes delighted with the extensive and favourable media coverage given to the visits. Conclusions: These media reports are likely to have influenced many who were exposed to them to believe that the evidence against smoking remained equivocal.